Empowering Patients with Type 2 Diabetes Mellitus through the Implementation of a Healthy Lifestyle with Morning Sunlight Exposure at Grandmed Hospital Lubuk Pakam (JURNAL PENGMAS KESTRA (JPK), 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease with an increasing prevalence and requires long-term management through pharmacological therapy and lifestyle modification. However, patient adherence to healthy lifestyle practices remains a major challenge. Morning sunlight exposure, as part of a healthy lifestyle, has the potential to support blood glucose control through metabolic mechanisms and circadian rhythm regulation. This Community Service Program aimed to empower patients with T2DM through education and mentoring on the implementation of a healthy lifestyle incorporating morning sunlight exposure at Grandmed Lubuk Pakam Hospital. The program employed an educative–participatory approach using a one-group pretest–posttest design involving 15 patients with T2DM. The intervention consisted of health education sessions, guided practice of morning sunlight exposure, and evaluation of participants’ knowledge, adherence, and blood glucose levels. The results showed a substantial improvement in participants’ knowledge, with the proportion of those in the good knowledge category increasing from 20.0% at pretest to 73.3% at posttest. Adherence to morning sunlight exposure was high, with 73.3% of participants classified as adherent. In addition, the mean blood glucose level decreased from 215 mg/dL before the intervention to 195 mg/dL after the intervention. In conclusion, this community service activity was effective in enhancing knowledge and health behaviors and demonstrated potential benefits in supporting glycemic control among patients with T2DM through a simple, practical, and sustainable empowerment-based approach.